A bestrophin‐like protein modulates the proton motive force across the thylakoid membrane in Arabidopsis. Issue 10 (20th April 2016) - Duan, Zhikun; Kong, Fanna; Zhang, Lin; Li, Wenjing; Zhang, Jiao; Peng, Lianwei
Abstract: During photosynthesis, photosynthetic electron transport generates a proton motive force (pmf) across the thylakoid membrane, which is used for ATP biosynthesis via ATP synthase in the chloroplast. The pmf is composed of an electric potential (ΔΨ) and an osmotic component (ΔpH). Partitioning between these components in chloroplasts is strictly regulated in response to fluctuating environments. However, our knowledge of the molecular mechanisms that regulate pmf partitioning is limited. Here, we report a bestrophin‐like protein (AtBest), which is critical for pmf partitioning. While the ΔpH component was slightly reduced in atbest, the ΔΨ component was much greater in this mutant than in the wild type, resulting in less efficient activation of nonphotochemical quenching (NPQ) upon both illumination and a shift from low light to high light. Although no visible phenotype was observed in the atbest mutant in the greenhouse, this mutant exhibited stronger photoinhibition than the wild type when grown in the field. AtBest belongs to the bestrophin family proteins, which are believed to function as chloride (Cl − ) channels. Thus, our findings reveal an important Cl − channel required for ion transport and homeostasis across the thylakoid membrane in higher plants. These processes are essential for fine‐tuning photosynthesis under fluctuating environmental conditions. Abstract : This work describes a novel bestrophin‐like chloride channel, AtBest, in chloroplasts. By mediating the influx of Cl − into thylakoid lumen, AtBest directly modulates the partitioning of proton motive force across the thylakoid membrane. This kind of ion transport and homeostasis is essential for fine‐tuning photosynthesis under fluctuating environmental conditions.